MATHEMATICAL CREATIVE DEVELOPMENT AMONG CHILDREN: A PRECUSOR FOR COUNSELLORS AND MATHEMATICS TEACHERS - Sani Sambo; Maruf O. Ibrahim (European Scientific Journal, ESJ, 2012)
This paper attempts to define Mathematical Creativity to establish whether every child is born creative mathematically or not and whether Mathematics teachers and counsellors should take necessary steps in developing and motivating children mathematical creative behaviour. Mathematics is a logical creation and imagination of the mind on space and figures for which every child need to exhibit at every piagetic level of development. Ironically the complaints on learners poor performance in Mathematics is so pathetic that counsellors and Mathematics teachers needs to bail out the situation. Hence this write up suggested 3 strategies for improving MCDAC and provided four (4) recommendations.